2004
DOI: 10.1103/physrevb.69.125315
|View full text |Cite
|
Sign up to set email alerts
|

Roto-vibrational spectrum and Wigner crystallization in two-electron parabolic quantum dots

Abstract: We provide a quantitative determination of the crystallization onset for two electrons in a parabolic two-dimensional confinement. This system is shown to be well described by a roto-vibrational model, Wigner crystallization occurring when the rotational motion gets decoupled from the vibrational one. The Wigner molecule thus formed is characterized by its moment of inertia and by the corresponding sequence of rotational excited states. The role of a vertical magnetic field is also considered. Additional suppo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 30 publications
1
38
0
Order By: Relevance
“…We hope that these variational functions will also be useful in developing methods of isolating spins of individual electrons and coupling them in a controllable manner in lateral quantum dots, as well as in other areas of research, e.g. to study with analytical expressions the formation of Wigner molecules 29,30 . We add two remark of a technical nature: First, in the case of a double quantum dot we were using the parameters β optimized in a single circular dot.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We hope that these variational functions will also be useful in developing methods of isolating spins of individual electrons and coupling them in a controllable manner in lateral quantum dots, as well as in other areas of research, e.g. to study with analytical expressions the formation of Wigner molecules 29,30 . We add two remark of a technical nature: First, in the case of a double quantum dot we were using the parameters β optimized in a single circular dot.…”
Section: Discussionmentioning
confidence: 99%
“…The mean field approaches were applied to the two-electron system also in the context of symmetry breaking they may induce and subsequent symmetry restoration by RPA 27 and projection techniques 28 . This theoretical problem, as well as the exact and numerical solutions mentioned above, proved relevant for a description of a Wigner molecule consisting of two electrons in a quantum dot 29,30 . 28,36,37 .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, later calculations confirmed that these effects are largely artifacts of the approximations used. 23,25,26,27,28,29,30 Projection methods were then used to restore symmetries as a second stage of the UHF calculations. 31,32,33,34,35 DFT has been pushed toward the large r s limit through the average spin density approximation.…”
Section: Introductionmentioning
confidence: 99%
“…Evidently, the effective confinement (Ω) increases with the magnetic field, and the contribution of the constant electron-electron interaction becomes weaker. Formally, if we introduce the characteristic length of the effective confinement ℓ Ω = /m * Ω, the parameter λ Ω = ℓ Ω /a * (R W at B = 0) determines the relative strength of the Coulomb interaction at a given ef- fective confinement [43]. This parameter decreases with an increase of the magnetic field strength.…”
Section: The Dependence Of the Measure E On The Magnetic Field Strmentioning
confidence: 99%